Whitstable Pearl. Series 2 [videorecording (DVD)] - Karlsen, Øystein (Acorn, 2023)
In Season One, Pearl juggled her commitments to the restaurant the eponymous Whitstable Pearl with her side hustle as a PI. In Season Two, Pearl prioritizes her detective work and transition from being a chef who solves crimes to a full-time investigator who just happens to own a restaurant. Pearl's cases overlap with DCI Mike McGuire's police investigations. Their relationship is charged by a determination to outdo each other, and a fiery mutual attraction. When they compete, sparks fly and tempers flare. When they work together, they make a hell of a team.